Accessibility of Microsoft Teams and Moodle Services for the Implementation of E-Learning for Students with Disabilities in Institutions of Higher Education in Ukraine - Oksana Khomik; Nataliia Bielikova; Svitlana Indyka; Oksana Kovalchuk; Viktor Halan-Vlashchuk (Lesya Ukrainka Volyn National University, 2021)
The current study investigates the ways to increase accessibility to higher education for students with disabilities. The importance of implementation e-learning for such students as one of the preconditions for effective social and psychological adaptation and further successful integration of persons with disabilities into society is emphasized. A survey of students with disabilities was conducted to identify their needs in educational process. The main difficulties that they overcome in the process of education in institutions of higher education are identified. The main peculiarities and advantages of the distance learning course «Adaptive Physical Education» are described created in the Moodle system. The differences and benefits of Microsoft Teams over the Moodle platform in the process of e-learning for students with disabilities are described. The process of organizing of «Adaptive Physical Education» distance learning course for students with disabilities on the Microsoft Teams platform and the purpose of implementation it in the institution of higher education are emphasized.